Retroperitoneal Plasmacytoma: A Case Report - Hossain, SM Amjad; Imtiaz, Mohammad Rafiz; Verma, Gopal (Journal of Bangladesh College of Physicians and Surgeons, 2012)
Solitary Extramedullary Primary Plasmacytoma (SEMPP) is a rare neoplasm. When diagnosed, head and neck region is its most likely location. Rarely, it may occur in the retroperitoneum. We report a case of an elderly male who was admitted in the department of surgery, Dhaka Medical College Hospital (DMCH) with a Solitary Extramedullary Retroperitoneal Primary Plasmacytoma (SEMRPP). Subtotal excision of the mass was done. The patient was referred to the department of Oncology DMC for radiotherapy. The first report of an extramedullary plasmacytoma was in 1905 in Taiwan. To the best of our knowledge, there was no report of a Solitary Extramedullary Retroperitoneal Primary Plasmacytoma (SEMRPP) from Bangladesh. DOI: http://dx.doi.org/10.3329/jbcps.v30i3.12467 J Bangladesh Coll Phys Surg 2012; 30: 167-169